Marketing via Social Networking Sites: A Study of Brand-Post Popularity for Brands in Singapore - Chua, Alton Yeow Kuan (2017)
Businesses often rely on social networking sites such as Facebook for marketing purposes. They create brand pages to disseminate brand-related posts among potential customers. Some brand-posts become popular by attracting substantial likes, comments and shares. In contrast, others remain largely ignored. To address this conundrum, this paper investigates the extent to which provision of incentives, as well as vividness and interactivity of brand-posts are related to their popularity in Facebook. Drawing data for brands in Singapore, three key findings are gleaned. First, brand-posts that provide incentives were unlikely to become popular. Second, vivid brand-posts were more likely to become popular vis-à-vis those that lacked vividness. Third, increase in interactivity of brand-posts up to an optimum level resulted in increasing popularity, beyond which there was a negative relationship.